Robotic‐assisted versus laparoscopic nephroureterectomy; a systematic review and meta‐analysis - Niall J. O'Sullivan; Ailish Naughton; Hugo C. Temperley; Rowan G. Casey (BJUI Compass, 2023)
Abstract Background Upper tract urothelial carcinoma (UTUC) is the malignant transformation of urothelial cells, from the renal calyces to the ureteral orifices. While the benefits of minimally invasive nephroureterectomy over their open counterpart have been established, the optimal technique remains a debate. We aimed to assess current evidence in the literature and compare outcomes between robotic‐assisted (RANU) and laparoscopic nephroureterectomy (LNU). Methods A systematic review of the literature was performed for studies comparing RANU and LNU for bladder cancer. Outcome measurements were recurrence rates (local and distal), positive margins, positive lymph node yield and perioperative outcomes. Meta‐analysis was performed using Review Manager 5. Results Our results demonstrate a significantly higher mortality rate in patients undergoing laparoscopic nephroureterectomy when compared with the robotic‐assisted approach for the treatment of UTUC (1.8% vs. 1.1%, p = 0.008); however, these results were inconsistent on sensitivity analysis and should therefore be interpreted with caution. No significant difference was observed for other outcomes. Conclusion The ideal approach to minimally invasive radical nephroureterectomy remains undetermined. Future research, ideally prospective randomised studies, should focus on long‐term outcomes, in particular recurrence, recurrence‐free survival, overall survival and the correlation between surgical technique and survival.